Employing Visible Light Communication for Evolving Network Performance of Next Cellular Systems - Mohammad R. Kadhum,; Heba Haboobi, (International Journal of Computers and Informatics, 2026)
A developed optical air interface for forthcoming short-range transmission in mobile networks, in which visible light communication (VLC) is utilized with orthogonal generalized frequency division multiplexing (OGFDM), is introduced, explored, and evaluated. The presented waveform, termed VLC-OGFDM, is used in a back-to-back optical wireless transceiver system that employs a high-frequency light carrier for optical modulation. The proposed design aims to overcome the channel bandwidth limitations of the waveform by maximizing the transmission bit rate in short-range optical wireless communication scenarios (indoor/outdoor) for future smart cities. Hence, although both the proposed VLC-OGFDM and the conventional OGFDM operate in the wireless domain, the VLC-OGFDM channel bit rate is significantly higher than that of OGFDM because it operates at a higher frequency (VLC) than radio frequency (RF). Besides, using optical rather than electrical modulation in wireless communications provides a high level of protection by avoiding interference with surrounding electrical signals. As such, the VLC-OGFDM waveform is a sophisticated version of the old-style RF-OGFDM, which enables the transmission of large amounts of data over short and safe distances. For electric-to-optic transformation and vice versa, the VLC-OGFDM requires auxiliary optical equipment such as a light-emitting diode (LED), an intensity modulator (IM), and a photodetector. The performance of the VLC-OGFDM system, including essential signal power, error level, and maximum transmission bit rate, is investigated relative to the electrical OGFDM. Ultimately, a MATLAB simulation based on the proposed system's parameters is used for performance validation.
Keywords: Visible Light Communication; Short-Range Transmission; Optical Wireless Transceiver; Indoor/Outdoor Communication